Micronutrients deficiency on the nutritional status of physalis (Research, Society and Development, 2022)
The plant Physalis peruviana L. presents a high added value, being able to be used from its root to the fruit itself. The roots and leaves are rich in medicinal properties and can be used in the pharmacological market. The supply of nutrients is one of the most important factors to be developed to increase the productivity of fisalis guaranteeing the quality desired by the market of consumption of its fruits. Knowledge of micronutrient requirements and nutritional efficiencies is relevant to the development of fisalis fertilization recommendation. The objective of this work was to evaluate the effect of micronutrients deficiencies on development and on nutritional status of fisalis plants. The experimental design was in randomized blocks, with three replicates. The treatments were composed of a complete nutrient solution containing macro and micronutrients and solutions with omission of one micronutrient with one plant per pot. The evaluations of the physiological characteristics were carried out at 35 days after the application of the treatments, and development and nutritional efficiency evaluations were performed at 150 days. Physiological characteristics of fisalis plants, such as photosynthetic rate, stomatal conductance, carbon consumption, internal carbon and water use efficiency, were limited with micronutrient subtraction. The micronutrients that most affected the cultivation of fisalis were B, Fe and Zn. The order of restriction of the development caused by the omission of micronutrients was: Fe> B> Zn> Mn> Cu.